A Theological Study of Old-Babylonian Personal Names - Bowes, Alpin Wendell (1987)
Ph.D. Dissertation; Supervisors: Stephen J. Lieberman, Sol Cohen, Stephen Geller; Order No. DA 8727174; DissAbstr. 48/09 (March 1988) 2424-A/2425-A.